Structure of a monolayer of molecular rotors on aqueous subphase from grazing-incidence X-ray diffraction - Kaleta, Jiří; Wen, Jin; Magnera, Thomas F; Dron, Paul I; Zhu, Chenhui; Michl, Josef (Proceedings of the National Academy of Sciences of the United States of America, 2018)
In situ grazing-incidence X-ray scattering shows that a monolayer of artificial rod-shaped dipolar molecular rotors produced on the surface of an aqueous subphase in a Langmuir trough has a structure conducive to a 2D ferroelectric phase. The axes of the rotors stand an average of 0.83 nm apart in a triangular grid, perpendicular to the surface within experimental error. They carry 2,3-dichlorophenylene rotators near rod centers, between two decks of interlocked triptycenes installed axially on the rotor axle. The analysis is based first on simultaneous fitting of observed Bragg rods and second on fitting the reflectivity curve with only three adjustable parameters and the calculated rotor electron density, which also revealed the presence of about seven molecules of water near each rotator. Dependent on preparation conditions, a minor and variable amount of a different crystal phase may also be present in the monolayer.
Keywords: grazing-incidence X-ray scattering; synchrotron radiation; aqueous-surface monolayer; X-ray reflectivity; molecular rotors